Let's solve the expression \(-4 (3 + 12^0) + 15^0\) step by step, correctly applying the Zero Power Rule.
-
According to the Zero Power Rule, any non-zero number raised to the power of 0 equals 1. Therefore:
- \(12^0 = 1\)
- \(15^0 = 1\)
-
Substituting these values into the expression: \[ -4 (3 + 1) + 1 \]
-
Now simplify inside the parentheses: \[ -4 (4) + 1 \]
-
Next, multiply \(-4\) by \(4\): \[ -16 + 1 \]
-
Finally, add \(-16\) and \(1\): \[ -15 \]
Therefore, the correct process of solving the expression is:
\(-4 (3 + 12^0) + 15^0 = -4 (3 + 1) + 1 = -4 \cdot 4 + 1 = -16 + 1 = -15\)
The correct statement from the options you provided is:
−4 (3 + 12^0) + 15^0 = −4 (3 + 1) + 1 = −4 ⋅ 4 + 1 = −16 + 1 = −15.